2015
DOI: 10.1007/698_2015_371
|View full text |Cite
|
Sign up to set email alerts
|

Safe Drinking Water? Effect of Wastewater Inputs and Source Water Impairment and Implications for Water Reuse

Abstract: The elimination of contaminants of emerging concern (CECs) during conventional wastewater treatment is not complete, and therefore, different amounts of these compounds are continuously released via wastewater effluents into the aquatic environment. This constitutes a major issue for water reuse, because these compounds can undergo transformation in the environment or during disinfection if reclaimed water is used for drinking water production. Different emerging contaminants, e.g., perfluorinated compounds, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 141 publications
1
1
0
Order By: Relevance
“…However, there are few reports of endocrine disruption by iodinated DHM (CIM in this study) in both human and animal studies because DHMs are not routinely detected in environments (Supplementary Figure 1). CIM may be as toxicologically relevant as regulated THMs and HAAs (Linge et al, 2013;Richardson and Postigo, 2015;Padhi et al, 2019). This study also found that CIM exposure resulted in the most substantial estrogenic inhibition in zERa.…”
Section: Discussionsupporting
confidence: 64%
“…However, there are few reports of endocrine disruption by iodinated DHM (CIM in this study) in both human and animal studies because DHMs are not routinely detected in environments (Supplementary Figure 1). CIM may be as toxicologically relevant as regulated THMs and HAAs (Linge et al, 2013;Richardson and Postigo, 2015;Padhi et al, 2019). This study also found that CIM exposure resulted in the most substantial estrogenic inhibition in zERa.…”
Section: Discussionsupporting
confidence: 64%
“…Alternatively, domestic wastewater properly treated could be recharged to suitable aquifers for subsequent recovery (indirect reuse) after holding the water for a time. 2 Such managed aquifer recharge is a natural water treatment process by which pollutants are removed by taking surface water or well-treated domestic wastewater into an aquifer for a long time and recovering it as drinking water or for irrigation purposes via a production well. This technique is considered to be environmentally friendly and costeffective, but there are trace organic compounds (TOrCs) that are incompletely removed or not removed in the aquifer.…”
Section: Introductionmentioning
confidence: 99%